RESTORATIVE JUSTICE FORMULATION POLICY IN THE JUVENILE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Maswandi, Maswandi; Ingratubun, Fitriyah; Ingratubun, Junaidi Abdullah (Faculty of Law, Universitas Diponegoro, 2023)
The aim of this research is to understand and evaluate restorative justice formulation policies in the juvenile criminal justice system in Indonesia. The judicial normative method is employed in this research approach. It can be concluded that in order to achieve restorative justice for every child, to create a balance between the interests of the perpetrator and the victim, and to also pay attention to the impact settlement of criminal cases so that they can live, grow, and develop, it is necessary to pay attention to how these provisions can be implemented in society, not just in the formulation of all laws and regulations.